1979
DOI: 10.1017/s002185960005379x
|View full text |Cite
|
Sign up to set email alerts
|

Response of grass swards to fertilizer N under cutting or grazing

Abstract: An experiment was conducted at six widely separated centres in England and Wales for 4 years to compare the response of a perennial ryegrass (cv. S. 23) sward to fertilizer N at input rates of 200, 400 and 600 kg N/ha under cutting-only or grazing-only management systems. Under both managements the yield response to N varied substantially and was always greater under cutting than grazing and the response was greater in the first than in subsequent years. Under cutting, significant responses were obtained from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 6 publications
5
11
0
Order By: Relevance
“…Overall, herbage production was lower in the grazing experiment than the amount that the cutting experiment would suggest was available for grazing. Similar to findings reported by Jackson and Williams (1979) and Binnie and Chestnutt (1991), this indicates that results from cutting experiments cannot be used to predict herbage DM yields and responses to N fertilizer under grazing conditions. In most regrowth periods, herbage growth was greater on the cut plots than the grazing plots.…”
Section: Discussionsupporting
confidence: 80%
“…Overall, herbage production was lower in the grazing experiment than the amount that the cutting experiment would suggest was available for grazing. Similar to findings reported by Jackson and Williams (1979) and Binnie and Chestnutt (1991), this indicates that results from cutting experiments cannot be used to predict herbage DM yields and responses to N fertilizer under grazing conditions. In most regrowth periods, herbage growth was greater on the cut plots than the grazing plots.…”
Section: Discussionsupporting
confidence: 80%
“…In several subsequent trials, the effects of splitting N doses and harvesting at 6-week intervals (' GM21') was investigated (Morrison 1980) and in a further development the response of grass swards to fertilizer N was made under both cutting-only and grazingonly managements ('GM22 '). This latter work was to show lower responses to N under grazing, suggesting that the results of fertilizer N experiments obtained under cutting could not be applied uncritically to grazed situations (Jackson & Williams 1979). A number of parallel studies were conducted elsewhere in Europe during the same period, notably in the Netherlands, which were to highlight the sward deterioration effects and subsequent herbage yield loss associated with very high N inputs (above 500 kg N/ha) (Prins 1984).…”
Section: G Ra S Sla N D Pro Du C T I Onmentioning
confidence: 99%
“…For example, higher herbage yield under cutting compared to grazing were observed by Binnie and Chestnutt [24] and Jackson and Williams [25]. In contrast, Creighton et al [26] found no difference in herbage production between grazing and cutting; Lantinga et al [27] found 10% higher herbage production in animal-grazed swards compared to cutting swards at 250 kg N ha -1 , whereas the difference disappeared at 550 kg N ha -1 .…”
Section: Introductionmentioning
confidence: 99%